Le régime d’assurance des catastrophes naturelles à l’épreuve des risques côtiers. Aléas versus aménités, le cas particulier des territoires littoraux - Eugénie Cazaux; Catherine Meur-Ferec; Cédric Peinturier (Cybergeo, 2019)
Created in 1982, the French natural catastrophe insurance scheme has made it possible to compensate for the "uninsurable" nature of certain major natural risks through private insurance contracts. However, for several years now it has been the subject of criticism and recurring reform attempts, justified by the rise in claims linked to meteorological events.This article examines the lack of financial consideration (additional premium and/or deductible modulation) of the degree of exposure to natural risks in this system, through a complete portrait of the "CatNat" regime and the analysis of data relating to orders recognizing the state of natural disaster for coastal hazards. This question is particularly relevant in coastal areas, where the degree of exposure to coastal risks and the amenities associated with proximity to the sea are closely linked.